Simultaneous magnetic dispersive micro solid phase extraction of valsartan and atorvastatin using a CMC-coated Fe3O4 nanocomposite prior to HPLC-UV detection: multivariate optimization. (21st October 2019) - Azadi, Ali; Ahmadi, Shahin
Abstract : In this study, a sensitive, rapid, accurate and practical procedure is established for determination of atorvastatin and valsartan from human biological fluids by dispersive micro solid phase extraction (D-μ-SPE) combined with HPLC-UV detector. Abstract : In the current study, a sensitive, rapid, accurate and practical procedure is established for determination of atorvastatin (AT) and valsartan (VAS) together from human biological fluids by dispersive micro solid phase extraction (D-μ-SPE) combined with a high-performance liquid chromatography-ultraviolet-visible detector (HPLC-UV). The Fe3 O4 @carboxymethyl cellulose (Fe3 O4 @CMC) nanocomposite was synthesized and employed as a magnetic adsorbent. The SEM, FT-IR, XRD, and VSM analytical techniques confirm the characteristics of the synthesized nanoadsorbent. The extraction process was optimized by central composite design (CCD) as the most popular response surface methodology (RSM). The optimum operational conditions are found in which pH = 7.0, 50 mg of the sorbent, sorption time 13 min, desorption time 5 min, sample volume 20 mL and a mixed solvent of 0.1 mL methanol, 0.2 mL acetonitrile, and 0.2 mL formic acid (3 : 100, v/v) as an efficient eluent solvent are used. Under the optimum experimental conditions, the linear dynamic ranges (LDRs), limits of detection (LODs), limits of quantitation (LOQs), enrichment factors (EFs) and relative standard deviations (RSDs) for VAS and AT were obtained to be as follows: EFs, 176 and 114; LODs, 2.4 and 2.1 μg L −1 ; LOQs 8.0 and 7.0 μg L −1, RSDs, 2.96 and 3.79 for AT and VAS, respectively; and LDRs, 10–2000 μg L −1 . The proposed method described is successfully implemented to determine trace amounts of AT and VAS for human serum and urine matrices.